Nutrient accumulation and export in teak (Tectona grandis L.f.) plantations of Central America - Fernández Moya, Jesús (2015)
This study aims at assessing the nutrient sustainability of highly productive teak plantations in Central America by analyzing the nutrient accumulation dynamics at different ages and the allocation patterns throughout a rotation period. Three teak plantations (28 stands of different ages) were selected in Costa Rica and Panama, and nutrient and biomass accumulation and allocation in different tree components (bole, bark, branches and foliage) were measured in the best performing trees between 1 and 19 years of age. A stand of 150 teak trees ha-1 at age 19 would accumulate (kg ha-1) 405 N, 661 Ca, 182 K, 111 Mg, 33 P, 53 S, 9 Fe, 0.47 Mn, 0.22 Cu, 0.92 Zn, 1 B; whereas the expected nutrient export by timber harvest (bole and bark) is (kg ha-1) 220 N, 281 Ca, 88 K, 63 Mg, 23 P, 39 S, 6 Fe, 0.13 Mn, 0.10 Cu, 0.21 Zn, 0.40 B. Our results sug - gest that teak nutrition should pay special attention to N and K, the nutrients most accumulated by teak along with Ca. In addition, P and B could also be limiting the productivity of planted teak stands due to their general soil deficiencies. Proposed models estimate the amount of nutrients removed from the site during timber harvests, information that can be used by plantation managers to avoid soil nutrient depletion, approaching sustainability in forest plantation management.